THE ROLE OF ABDURRAHMAN WAHID IN CREATING ISLAMIC POST-TRADITIONALIST PARADIGM IN INDONESIA - Tajuddin, Muhammad Saleh (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2019)
This writing describes Abdurrahman Wahid’s thought and his influence in creating a new paradigm of thought among the new generation of Nahdlatul Ulama (NU) organization in Indonesia. This writing applies qualitative techniques through library and field research. Primary data are collected through observation, interviews, and documentation, while secondary data are collected through textbooks, journals, and the internet. The data are analyzed by descriptive analysis. NU organization is known as a traditionalist Islamic organization vis a vis an Islamic modernist organization Muhammadiyah. Wahid wants Muslim integrity to become a good community, such as tolerate and respect other people. Every Muslim has to respect other people and struggle for justice, egalitarianism and protect weak people. The methodology of this writing is qualitative research. In fact, Wahid’s thought of egalitarianism, tolerance, and liberalism influences the young generation of NU organization that creates a thought of school, namely post-radisionalist (Postra). Postra is a kind of leap thought among NU generation that carries out themes, such as, egalitarianism, tolerance, liberalism, civil society, and democracy. In South Sulawesi, the NU young generation establishes a non-government organization (NGO), which is called Lembaga Advokasi Pendidikan Anak Rakyat that carries out the same theme that of Wahid’s.Keywords: Abdurahman Wahid; Nahdlatul Ulama; Islamic Post-Traditionalist: LAPAR organization: الملخصتوضح هذه المقالة أفكار عبد الرحمن وحيد وتأثيرها في خلق وجهة النظر الجديد للتفكير جيل الشباب في النهضة العلماء (NU) بإندونيسيا. تطبق هذه المقالة تقنيات نوعية من خلال الدراسة المكتبية والمجال البحثي النوعي والمصادر الرئيسية لها عبارة عن مجموعة من طرق إجراء الاستطلاعات بحيث تم العثور على بياناتها الأساسية من خلال المراقبة والمقابلات والتوثيق ، وأما مصادرها أو مراجعها الثانوية فهي تستمد من الكتب المدرسية والمجلات العلمية والإنترنت، فقد تم تحليل البيانات المذكورة باستخدام المنهج التحليلي. ومن العروف أن